CHALLENGES IN CHOICE OF THE TREATMENT STRATEGY FOR PATIENTS WITH RECURRENT PSEUDOMYXOMA PERITONEI - A. G. Abdullaev; М. M. Davydov; N. A. Коzlov (Сибирский онкологический журнал)
Pseudomixoma peritonei is a rare type of peritoneal carcinomatosis accompanied by accumulation of mucus and high recurrence rate and in some cases complicated with intestinal obstruction. In the last 10–15 years, there has been observed a significant improvement in overall survival of patients with recurrent pseudomyxoma, who underwent cytoreductive surgery in combination with intraperitoneal chemotherapy. However, the frequency of recurrences of peritoneal pseudomyxoma after optimal cytoreduction can reach 80–90 % in the first 2 years.The purpose of the study was to analyze the results of combined therapy (cytoreductive surgery and hypothermic intraperitoneal chemoperfusion) in patients with recurrent pseudomyxoma peritonei, who previously underwent cytoreductive surgery.Material and Methods. The study included 43 patients previously undergoing cytoreductive surgery for pseudomyxoma peritonei in the Thoracic Oncology Department of the N.N. Blokhin National Medical Research Center of Oncology.Results. Re-operations were performed in 11 of the 43 patients with recurrent pseudomixoma peritonei after previously performed cytoreductive surgery. Repeated intraperitoneal chemoperfusion with hyperthermia was performed in 6 patients. Of the 11 reoperated patients, 7 had a complete cytoreduction (CC-0), recurrence was detected within 22 to 47 months; 2 patients had CC-1 and recurrence was observed within 12 and 15 months. Optimal cytoreduction (CC0-1) was achieved in 7 of the 11 patients. The maximum follow-up period was 44 months. Recurrence was noted in 9 patients, while the majority of patients had a satisfactory quality of life. Two patients showed signs of partial intestinal obstruction. None of the patients died during the follow-up period. In two patients with optimal (CC-0) cytoreduction, there were no signs of disease progression 9 and 15 months after re-surgery. One-year disease-free survival rate was 51 %.Conclusion. Repeated surgeries for recurrent pseudomyxoma present a great challenge for surgeons due to the difficulty in achieving optimal cytoreduction. Optimal cytoreduction in initial surgery should be considered as the main condition for repeated surgery. Moreover, additional criterion for a favorable prognosis is the time to progression of disease.